2021
DOI: 10.1088/1361-6528/ac13e7
|View full text |Cite
|
Sign up to set email alerts
|

Energy recycling under ambient illumination for internet-of-things using metal/oxide/metal-based colorful organic photovoltaics

Abstract: Colorful indoor organic photovoltaics (OPVs) have attracted considerable attention in recent years for their autonomous function in internet-of-things (IoT) devices. In this study, a solutionprocessed TiO 2 layer in a metal-oxide-metal (MOM) color filter electrode is used for light energy recycling in P3HT:ICBA-based indoor OPVs. The MOM electrode allows for tuning of the optical cavity mode to maximize photocurrent production by modulating the thickness of the TiO 2 layer in the sandwich structure. This appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…It was observed that the performed perovskite layer on silicon wires is continuous, compact, and free of air bubbles and contaminants. Additionally, as indicated in the literature [2,3,5,12], the front cell should be thick enough to absorb all photons with the energy above the bandgap in a single pass of light so the MAI is well suited for initial proof-of-concept tandem devices when the layer thickness is approximately 1 µm thick, which is still experimentally challenging while maintaining a high material quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the performed perovskite layer on silicon wires is continuous, compact, and free of air bubbles and contaminants. Additionally, as indicated in the literature [2,3,5,12], the front cell should be thick enough to absorb all photons with the energy above the bandgap in a single pass of light so the MAI is well suited for initial proof-of-concept tandem devices when the layer thickness is approximately 1 µm thick, which is still experimentally challenging while maintaining a high material quality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to obtain a higher efficiency of the photovoltaic conversion, the lower parasitic absorption must be obtained by the reduction in losses from series resistance through the transport of lower current at higher voltage [4]. In the 2T structure, it is necessary to use only two contacts including one (on the top sub-cell) transparent to light, therefore, the use of transparent electrodes is necessary and cannot be ignored [3,[10][11][12]. Sub-cells in the 2T structure are connected by a tunnel junction or a recombination layer into a monolithic cell.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite solar cells are photovoltaics with solution processed active layer, one of several recently studied technology. The other broadly investigated photovoltaics with solution processed active layer, include photovoltaics based on the organic semiconductors as active layers [ 20 , 21 , 22 ]. All of these PSC devices are supposed to have high power efficiency, high stability, and large-scale applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Microgrid systems located in a remote area could have fewer prerequisites due to the nature of the loads, such as streetlight and domestic needs, as compared to the massive electrical network or macro network. The latest trend of power generation is by the use of renewable energy sources due to the fact that they are clean, friendly and naturally replenish on the human time scale [1][2][3][4]. Countries across the globe are exploring their ecological approaches to power sharing to reduce total dependence on the conventional method of power generation.…”
Section: Introductionmentioning
confidence: 99%
“…Another option by which electrical power can be supplied to the remote area where there is no opportunity for grid connection is by making use of generating sets; this alternative is not encouraged because of the potential release of harmful and poisonous gases to the surrounding area, which can contribute to global warming [3]. Scientists, researchers and industrialists have shown a great interest in microgrids with RDG development due to the advantages it can offer in terms of sustainability, power quality and simple design implementation [4]. Any microgrid is an active network that connects renewable energy resource and loads.…”
Section: Introductionmentioning
confidence: 99%